2018
DOI: 10.1007/978-3-319-99181-8_103
|View full text |Cite
|
Sign up to set email alerts
|

Elementary, My Dear Watson: The Use of Artificial Intelligence in Marketing Research: An Abstract

Abstract: In this paper, the authors demonstrate how IBM Watson, a super computer that uses artificial intelligence (AI), can be used in academic and managerial research. A brief description of how Watson originated and operates is followed by four examples of how Watson can be used in academic marketing research. The first two examples use Watson's personality and insight services to analyze qualitative depth interviews. The last two examples use Watson's emotion and sentiment analysis on textual data and qualitative d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…1995 (Ives et al 1995 (Goh et al 2009) Mobile marketing 2010 (Guo et al 2010) (Nakhata 2015) Freemium (ICIS) Freemium (AMS) 2012 2016 (Liu et al 2012) (Cziehso and Schaefers 2017) Mobile shopping 2013 (Swilley and Cowart 2015) Mobile commerce on tablet 2013 (Han et al 2013) Mobile Self-service Technologies 2006 (Treiblmaier and Dickinger 2006) Mobile banking 2011 (Nel et al 2015) User Generated Content (UGC) 2003 (ICME) 2008 (ICIS) (Koskinen 2003) (Oh et al 2008) Online reviews 2004 (Dellarocas et al 2004) (Beser et al 2019) Artificial intelligence in marketing 2018 (Pitt et al 2018) Big Data 2014 (Hristova 2014) Adaptive Big Data analytics 2014 (Zhang et al 2014) Social Media 2009 (Xu and Zhang 2009) Social media influencers 2010 (Lindsay et al 2015) Social Media Marketing 2012 (Bauer et al 2015) "Journal of Digital and Social Media Marketing" (Liu et al 2007) (Blazauskas et al 2017) Augmented reality with customers 2016 (Poushneh 2017) Technology Marketing" 3D virtual shopping environments 2013 (Mann et al 2015) B2B virtual trade shows 2010 (Gabisch 2015) Blockchain 2016 (Avital et al 2016) Cryptocurrencies 2018 (Mauri et al 2018) IT Enabled Cocreation 2008 (Grace et al 2008…”
Section: Tables and Figuresmentioning
confidence: 99%
“…1995 (Ives et al 1995 (Goh et al 2009) Mobile marketing 2010 (Guo et al 2010) (Nakhata 2015) Freemium (ICIS) Freemium (AMS) 2012 2016 (Liu et al 2012) (Cziehso and Schaefers 2017) Mobile shopping 2013 (Swilley and Cowart 2015) Mobile commerce on tablet 2013 (Han et al 2013) Mobile Self-service Technologies 2006 (Treiblmaier and Dickinger 2006) Mobile banking 2011 (Nel et al 2015) User Generated Content (UGC) 2003 (ICME) 2008 (ICIS) (Koskinen 2003) (Oh et al 2008) Online reviews 2004 (Dellarocas et al 2004) (Beser et al 2019) Artificial intelligence in marketing 2018 (Pitt et al 2018) Big Data 2014 (Hristova 2014) Adaptive Big Data analytics 2014 (Zhang et al 2014) Social Media 2009 (Xu and Zhang 2009) Social media influencers 2010 (Lindsay et al 2015) Social Media Marketing 2012 (Bauer et al 2015) "Journal of Digital and Social Media Marketing" (Liu et al 2007) (Blazauskas et al 2017) Augmented reality with customers 2016 (Poushneh 2017) Technology Marketing" 3D virtual shopping environments 2013 (Mann et al 2015) B2B virtual trade shows 2010 (Gabisch 2015) Blockchain 2016 (Avital et al 2016) Cryptocurrencies 2018 (Mauri et al 2018) IT Enabled Cocreation 2008 (Grace et al 2008…”
Section: Tables and Figuresmentioning
confidence: 99%
“…As the paper unfolds, however, it becomes increasingly clear that the paper moves away from the traditional approaches, best-practice, and wisdom of the consumer research and other insight-based communities, such as sensory evaluation in the world of food, cosmetics, and other consumer products. Rather, the paper moves towards a systemized approach which requires absolutely no knowledge about a topic, an approach easy to use even by school children as young as eight years old [23,24]. The focus is on a process which requires literally no expertise to master, a process which starts with questions and exports actionable answers.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, IA is a technology quite new in comparison with others such as AR and VR, which means that analyzing the impact of IA on digital consumer behavior patterns is a very broad area of study. The fusion of AI and marketing will certainly grow (Pitt et al 2018 ; Wirth 2018 ; Vishnoi and Bagga 2019 ) in such a way that investigating the consumer journey facilitated by AI technology can help academia to obtain information on the benefits of IA technology. Some other topics for research that researchers have identified in this field are as follows: to use smart algorithms for in-depth study of automated marketing concepts (Dumitriu and Popescu 2020 ) and to observe how multichannel AI systems can help to create a lean or a more intelligent technology (Cosmin Tănase 2018 ).…”
Section: Directions For Future Researchmentioning
confidence: 99%